Stocks for All: People's Capitalism in the Twenty-First Century - Mäntysaari, Petri (De Gruyter, 2021)
Public stock markets are too small. This book is an effort to rescue public stock markets in the EU and the US. There should be more companies with publicly-traded shares and more direct share ownership. Anchored in a broad historical study of the regulation of stock markets and companies in Europe and the US, the book proposes ways to create a new regulatory regime designed to help firms and facilitate people's capitalism. Through its comparative and historical study of regulation and legal practices, the book helps to understand the evolution of public stock markets from the nineteenth century to the present day. The book identifies design principles that reflect prior regulation. While continental European company law has produced many enduring design principles, the recent regulation of stock markets in the EU and the US has failed to serve the needs of both firms and retail investors. The book therefore proposes a new set of design principles to serve contemporary societal needs.